Artificial Intelligence and its Impact on Social Policy-Making - ALKHAZA’LEH, YOUNIS MOHAMMAD SALAMEH (Journal of Ecohumanism, 2025)
This study aims to analyze the role of artificial intelligence (AI) in shaping social policies, focusing on its impacts on poverty, unemployment, education, and healthcare. The research explores the concept, origins, types, and dimensions of AI, as well as the stages of social policymaking. It highlights how AI technologies contribute to building simulation models that support governmental decision-making and enhance civic engagement through interactive platforms that allow citizens to express their opinions and participate in policymaking. Additionally, AI facilitates monitoring and analyzing social trends, enabling governments to respond swiftly to social and economic changes and crises, such as pandemics and natural disasters. The study concludes that AI plays a crucial role in improving transparency, building trust in governments, and offering innovative solutions to social challenges.